-(-9)+2y+(-9)+6=

Simple and best practice solution for -(-9)+2y+(-9)+6= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-9)+2y+(-9)+6= equation:


Simplifying
-1(-9) + 2y + (-9) + 6 = 0

Multiply -1 * -9
9 + 2y + (-9) + 6 = 0
9 + 2y + -9 + 6 = 0

Reorder the terms:
9 + -9 + 6 + 2y = 0

Combine like terms: 9 + -9 = 0
0 + 6 + 2y = 0
6 + 2y = 0

Solving
6 + 2y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 2y = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 2y = 0 + -6
2y = 0 + -6

Combine like terms: 0 + -6 = -6
2y = -6

Divide each side by '2'.
y = -3

Simplifying
y = -3

See similar equations:

| 7w-3(4w+8)=7 | | X^2-6Y+2x+y^2=9 | | 23=2b+5b | | x+2x(5)+2x(2x)(10)+2x(2x)-3(25)+2x(100)+2x(500)=9382 | | 21x=6+17x-26 | | 2m^2-5m-2=0 | | 3j-1+6=0 | | 4m-3m=2 | | g(x)=36 | | 8-2x-3x=-16-8x | | 2(x+2)=5x-3 | | -6(3z-7)=33 | | 36-(3x+4)=2(x+4)+x | | x-5x+4x-7x= | | x^3-5x^2+2x=-1 | | 3+2k=17 | | x=7ln(y^2-48) | | 2w^2+7w=0 | | 7x=19(2x-7) | | -2x-x+1=0 | | 0.2x^5-2x^3+1.8x+5=0 | | 7+12p=-5 | | -2x-6=2-4-(x-1) | | 0.2x^5-2x^3+1.8x+2=0 | | R^2+10r-30=0 | | 3a+23=53 | | 4x^3+22x^2+24x=0 | | 2x^2-sinx+1=0 | | 16x^2-54x-16=0 | | 1-6x-3x=-17 | | (15)(13)+(15)(7)= | | 2a-18=34 |

Equations solver categories